(untitled) (Journal of Pharmaceutical Negative Results, 2022)
During the last century a great deal of work has been done in the study of the poem Yusuf Has Hajib's "Kutadgu Bilig", which was the first Turkic manuscript. In Uzbekistan, Professor Kayum Karimov did some research on translating this work in Uzbek and presented it in a language that is understandable to readers. On the other hand, this poem has been translated into several languages ​​of the world, and much more has been done. However, there are some disadvantages in conveying its essence. These shortcomings can be seen in the fact that translations in different languages ​​are lost in translation, with some artifacts being lost. This article compares the artistic content of the box knowledge with comparative analysis in foreign languages. Working on a scientific article, three versions were analyzed and studied. Their bytes were compared. As a result, every translation has some differences. But we can see the similarity between the translations, especially in translations by May and Ivanov. Because, separately, Walter May has translated this work from a Russian translation by Ivanov. Given that both of the above translations are translated in partnerships, we can see that they have some artwork in place. This is evident in the translation by Robert Denkoff. The main reason was that Denkoff translated this work in prose. Illustrated by specific bytes of the work, it provides a comprehensive comparison of the artistic tools used, including illustrations and epithets, in translations from four books to three different languages. Finally, it became clear that the shortcomings of some translators had a profound effect on the translation of the work without affecting the translation.